"On a night like this": A mixed‐methods approach to understanding high‐risk drinking events in college students. (30th April 2022) - Garcia, Tracey A.; Hultgren, Brittney A.; Canning, Jessica R.; Gilson, Michael S.; Larimer, Mary E.
Abstract: Background: Previous research indicates college students report heavier drinking on certain events (e.g., 21st birthday). While past research has identified heavier drinking events, students' own reports of which events are associated with elevated drinking remains understudied. The current study utilized mixed methods to explore potential high‐risk drinking events (HRDE) for college student drinkers and how these events differed from typical drinking and each other. Methods: College student drinkers ( N = 204) reported the number of drinks they consume on nine predetermined events (e.g., Halloween). Students also responded to open‐ended questions listing five events during which they had elevated drinking and indicating the amount consumed on each event. Open‐ended responses were coded into similar event categories. Descriptive statistics for drinks consumed were calculated for predetermined and coded open‐ended events. Chi‐square analyses assessed differences in endorsement of open‐ended events by birth sex, age group, and Greek membership. Two multilevel count regressions assessed within‐person differences in number of drinks consumed between participants' typical drinking occasions and (1) highly endorsed open‐ended events and (2) predetermined events. Results: For all open‐ended event categories, average number of drinks consumed exceeded heavy episodic drinking thresholds; however, there was substantial variability. Comparing predetermined events to participants' typical drinking indicated elevated drinking on participants' birthdays, New Year's Eve, Halloween, Finals, and Spring Break; significant differences between events also emerged. Comparison of open‐ended categories to participants' typical drinking indicated elevated drinking on birthdays, celebrations, parties, and holidays; however, there were no significant differences between open‐ended events. Conclusions: Students who drink alcohol report heavier drinking on specific calendar‐based events (e.g., Spring Break). However, students also report non‐calendar‐related events (e.g., non‐specific parties) as some of their highest drinking events. More research is needed to understand how intervention and prevention programs can be adapted to target both known calendar‐based HRDE, and unknown, idiosyncratic HRDE. Abstract : College student drinkers reported on both calendar‐based and non‐calendar based, self‐determined high‐risk drinking events (HRDE). Qualitative assessment of self‐nominated HRDE indicate diverse HRDE categories. Results indicated increased drinking in all self‐reported HRDE and some calendar HRDE. Differences between events were also determined. Results suggest HRDE may be best explained through a social‐ecological approach influenced by different hierarchical levels (e.g. shared calendar‐based events, regional‐, and campus‐specific events, and personal events). At least one open‐ended question should be considered when examining HRDE.